Plants of the Araceae family for malaria and related diseases: a review - G. FRAUSIN; R. B. S. LIMA; A. F. HIDALGO; L. C. MING; A.M. POHLIT (Universidade Estadual Paulista, 2015)
ABSTRACTIn the current work we performed a review of the Araceae family species traditionally used to treat malaria and its symptoms. The aim is to reveal the large number of antimalarial Araceae species used worldwide and their great unexplored potential as sources of antimalarial natural products. The SciFinder Scholar, Scielo, PubMed, ScienceDirect and Google books search engines were consulted. Forty-three records of 36 species and 23 genera of Araceae used for malaria and symptoms treatment were found. The neotropical genera Philodendron Schott and Anthurium Schott were the best represented for the use in the treatment of malaria, fevers, liver problems and headaches. Leaves and tubers were the most used parts and decoction was the most common preparation method. The extracts of Araceae species inhibit the in vitro growth of the human malaria parasite, the Plasmodium falciparum Welch, and significant median inhibitory concentrations (IC50) for extracts of guaimbê-sulcado (Rhaphidophora decursiva (Roxb.) Schott), aninga (Montrichardia linifera (Arruda) Schott), Culcasia lancifolia N.E. Br. and forest anchomanes (Anchomanes difformis (Blume) Engl.) have been reported demonstrating the antimalarial and cytotoxicity potential of the extracts and sub-fractions. In the only report about the antimalarial components of this family, the neolignan polysyphorin and the benzoperoxide rhaphidecurperoxin presented strong in vitro inhibition of the D6 and W2 strains of Plasmodiumfalciparum (IC50 = 368-540 ng/mL). No live study about antimalarial activity in animal models has been conducted on a species of Araceae. More bioguided chemical composition studies about the in vitro and also thein vivo antimalarial activity of the Araceae are needed in order to enhance the knowledge about the antimalarial potential of this family.